A high-performance low-mechanical anisotropy rare earth permanent magnet and its preparation method

By adding Sm2O3 or ZrO2 particles to rare earth cobalt permanent magnet materials, the grain coarseness is suppressed and the bending strength of rare earth cobalt permanent magnet materials is improved, and the problems of brittleness and mechanical properties are solved, and high performance and low mechanics are achieved The preparation of anisotropic rare earth permanent magnets significantly improves the bending strength and magnetic properties.

CN118588392BActive Publication Date: 2025-01-07SOUTHWEST INST OF APPLIED MAGNETICS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411037118.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-01-07
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

Rare earth cobalt permanent magnet materials limit their wider application due to their intrinsic brittleness and mechanical properties. The prior art is not suitable for rare earth cobalt permanent magnet materials when improving their mechanical properties.

Method used

By adding a specific ratio of Sm2O3 or ZrO2 to the rare earth cobalt permanent magnet material as the second phase particles, the grain coarseness is inhibited, the flexural strength of the alloy is improved, and high-performance, low-mechanical anisotropic rare earth permanently obtained through magnetic field molding and heat treatment. magnet.

Benefits of technology

It significantly improves the bending strength of rare earth permanent magnets and reduces the anisotropy difference. The maximum bending strength reaches nearly 200MPa, with excellent magnetic performance and anisotropy difference of less than 25MPa, exceeding the industry standard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118588392B_ABST
    Figure CN118588392B_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance low-mechanical anisotropy rare earth permanent magnet and a preparation method thereof, belonging to the technical field of rare earth permanent magnet materials. The raw materials used are composed of a main alloy and a second phase alloy, wherein the chemical composition of the main alloy is Sm(Co bal Fe x Cu y Zr k ) z , wherein z=6.90~8.0, x=0.10~0.34, y=0.05~0.1, k=0.01~0.03, the second phase alloy is oxide particles, such as Sm2O3 or ZrO2; the present invention adds a certain amount of specific second phase particles, and the alloy magnetic properties of the permanent magnet prepared are excellent (( BH ) max ³24MGOe), the mechanical strength of the alloy samples in three different orientation directions can be significantly improved, the maximum bending strength reaches nearly 200MPa, and the anisotropy difference is less than 25MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare earth permanent magnet materials, and in particular to a high-performance low mechanical anisotropy rare earth permanent magnet and a preparation method thereof. Background Art

[0002] Rare earth cobalt permanent magnet materials with high magnetic energy product, high coercivity, good corrosion resistance, excellent thermal stability and other characteristics are the core materials of control systems such as missiles, rockets, satellites, and aircraft. They are also key materials for modern radar, microwave communications, and electronic warfare systems. They are widely used in military electronic equipment such as avionics and electromagnetic space warfare. Rare earth permanent magnets play a key role and are irreplaceable in modern weapons and equipment. However, due to its cleavage transgranular fracture mode, rare earth cobalt permanent magnet materials have intrinsic brittleness, which greatly limits the wider application of rare earth permanent magnets.

[0003] Li Wei et al. studied Sm2Co 17 Fracture mode of anisotropic magnet. According to the analysis of cross-sectional morphology, the fracture mode of the magnet is transgranular cleavage fracture, and river patterns and cleavage steps can be clearly observed in the fracture. 17 Magnet is an anisotropic material, and its fracture behavior also shows anisotropy. Mechanical properties testing is usually carried out in accordance with the national standard GB / T31967.2-2015 Test methods for physical properties of rare earth permanent magnet materials Part 2: Determination of flexural strength and fracture toughness. The flexural strength and fracture toughness specimen sizes are ( h × b × L )5×6×20 and ( B × W × L )5×10×45. Therefore, when the orientation direction is different from the direction of the mechanical test specimen, its mechanical properties have directional differences. The results show that when the specimen orientation c With span direction L When parallel, the mechanical properties are generally poor. The statistical results of mechanical tests show that c / / L Direction c / / h and c / / b The orientation direction is often lower than 40MPa, which leads to great risks to the use of the magnet when the orientation direction is subjected to stress.

[0004] Chinese patent CN102568738A discloses that by microalloying (adding Ti and Co elements), a second phase (TiB2, NdFeCoTi) dispersed in the crystal is formed in the alloy, the mechanical properties of the alloy are increased, and finally a NdFeB magnet with a bending strength of not less than 500MPa is obtained; Chinese patent CN113936880A discloses that by adding Zr element to NdFeB magnet, Zr is precipitated in the R-rich phase at the grain boundary in the form of fibrous compound through a certain process, the strength of the R-rich phase is increased, and the bending strength of the magnet is increased; however, the above two methods for improving the mechanical strength of NdFeB magnets are not suitable for rare earth cobalt permanent magnet materials.

[0005] Chinese patent CN113517104A discloses adding auxiliary phase alloy RE to rare earth cobalt permanent magnet material. 1-u-v- w Fe u Cu v TM w , wherein RE is selected from one or more of Sm, Nd, Pr, Dy, Tb, Gd and Ho, and the Sm and Cu elements in the magnet diffuse from the grain boundary phase to the interior of the alloy main phase grains, thereby improving the cellular structure of the alloy and optimizing the magnetic properties of the alloy. The low melting point auxiliary phase also forms a bonding layer between the grains to improve the mechanical properties of the magnet. The prepared samarium cobalt permanent magnet material has excellent remanence, coercive force and squareness as well as good mechanical properties. However, the anisotropic characteristics of the mechanical properties (large directional differences in mechanical properties) of the rare earth permanent magnet prepared by this method have not been significantly improved. Summary of the invention

[0006] One of the purposes of the present invention is to provide a high-performance low-mechanical anisotropy rare earth permanent magnet to solve the above-mentioned problems.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: a high-performance low-mechanical anisotropy rare earth permanent magnet, the raw materials used are composed of a main alloy and a second phase alloy, wherein the chemical composition of the main alloy is Sm(Co bal Fe x Cu y Zr k ) z , where z=6.90~8.0, x=0.10~0.34, y=0.05~0.1, k=0.01~0.03, bal+x+y+k=1, and the second phase alloy is Sm2O3 or ZrO2.

[0008] As a preferred technical solution, second phase particles with good chemical compatibility with the main phase are selected. The second phase particles do not react chemically with the main phase, so the effect on the magnetic properties is small. At the same time, the second phase particles can inhibit grain growth during sintering and improve the mechanical properties of the magnet. Preferably, the second phase particles are Sm2O3 or ZrO2, and the addition amount of Sm2O3 is 1.0% to 2.0wt% of the main alloy, and the addition amount of ZrO2 is 1.0 to 3.0wt% of the main alloy.

[0009] The present invention adds a proper proportion of specific second phase particles, which are mainly distributed at the alloy grain boundaries, and inhibits the coarsening of alloy grains through the Zener effect during sintering and heat treatment. , F p is the pinning force, f is the volume fraction of the second phase particles, γGB is the grain boundary energy per unit area, and r is the radius of the second phase particles. The smaller the particle size of the second phase particles, the larger the volume fraction, the more diffuse the distribution, the stronger the pinning effect, and the better the inhibitory effect on the coarsening of alloy grains. Figure 1 and Figure 2 As shown in the metallographic structure diagram of the alloy magnet, in the figure, the precipitated phase 1 is mainly a Zr-rich 2:7 phase, which is a common precipitated phase in samarium-cobalt alloys, not easy to corrode, and the metallographic phase is white. The second phase particles 2 are samarium oxide or zirconium oxide particles, which are easy to corrode and the metallographic phase is black. Figure 1 This is the organization diagram of the magnet alloy without adding the second phase particles 2, and the average grain size is about 40 mm; Figure 2 The black particles in the figure are the second phase particles 2 added to the alloy, which are mainly distributed at the grain boundaries of the alloy. The average grain size is about 10 mm. Figure 1 and Figure 2 By comparison, it can be seen that adding second phase particles with good chemical compatibility to the alloy can significantly refine the alloy structure. The fine alloy grains can inhibit crack propagation during the alloy fracture process, and the energy absorption effect is more obvious, so the alloy exhibits higher bending strength.

[0010] The present invention improves the bending strength of the magnet by reducing the magnet grain size. c Parallel to span direction L When the bending strength of the material is generally the lowest, c / / b and c / / hThe direction is higher because the magnet is most likely to cleave after being subjected to tensile stress along the orientation direction. The present invention reduces the grain size, improves the magnet, and reduces the influence of the basal surface being easily cleaved by tensile stress in the orientation direction, thereby achieving the purpose of reducing the anisotropy difference in the three directions.

[0011] The second purpose of the present invention is to provide a method for preparing the above-mentioned high-performance low-mechanical anisotropy rare earth permanent magnet, the technical scheme adopted is that the steps include main alloy batching, main alloy smelting into alloy ingots, main alloy crushing, main alloy grinding, adding second phase alloy, mixing, molding, sintering, and heat treatment.

[0012] As a preferred technical solution, the raw materials used are metal samarium with a purity of 99.9wt%, metal cobalt, pure iron rod, electrolytic copper, and metal zirconium.

[0013] As an optimal technical solution, the main alloy abrasive adopts an air flow mill, and the parameters of the air flow mill are: the speed of the work separation wheel is 2000-6000r / min, the working fluid pressure is 0.4-0.8MPa, the grinding chamber pressure is 0.02-0.06MPa, and the gas is high-purity nitrogen, and finally an alloy powder of 2-5mm is produced.

[0014] As a preferred technical solution, the particle size of the added second phase alloy is 0.1 to 0.9 mm.

[0015] As a preferred technical solution, the mixed materials are uniformly mixed under the protection of inert gas, steel balls with a ball radius of 8 to 15 mm are added to the mixing tank, the amount of steel balls added is steel ball mass / powder mass = 1 / 2 to 1 / 3, and the mixing time is not less than 8 hours.

[0016] As a preferred technical solution, the forming is magnetic field forming, using a semi-automatic magnetic field forming press, the evenly mixed alloy powder is magnetically formed into blocks or cylinders, and cold isostatic pressing is performed to obtain a green body; the magnetizing current used is 60-80A, the demagnetizing current is 20-30A, the forming pressure is 5-12MPa, and the isostatic pressure is 200-250MPa.

[0017] As a preferred technical solution, the vacuum degree during the sintering process is better than 5×10 -3 Pa, keep the sintering temperature at 1090-1220°C for 0.5-2h, cool to 1000-1198°C for solution treatment, keep it for 0.5-2h, quickly cool to room temperature, and finally obtain a solid solution magnet.

[0018] As a preferred technical solution, the vacuum degree during the heat treatment process is better than 5×10 -3Pa, keep the heat treatment temperature at 790-810°C for 20-30h, cool to 380-420°C, keep it for 10-20h, cool to room temperature, and obtain the final magnet sample.

[0019] Compared with the prior art, the present invention has the advantages that: by adding a certain amount of specific second phase particles, the alloy magnetic properties of the permanent magnet prepared by the present invention are excellent (( BH ) max ³24MGOe), the mechanical strength of the alloy has been significantly improved, the anisotropy difference of the bending strength of the magnet alloy is less than 25MPa, and the maximum bending strength reaches nearly 200MPa, which is significantly better than the current industry level. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a metallographic structure diagram of a magnet without adding a second phase in Comparative Example 1;

[0021] Figure 2 This is the metallographic structure diagram of the magnet with 2wt% Sm2O3 second phase added in Example 3; DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with embodiments.

[0023] Embodiment 1:

[0024] A high-performance low-mechanical anisotropy rare earth permanent magnet, the raw materials used in its preparation are: Sm(Co 0.675 Fe 0.22 Cu 0.08 Zr 0.025 ) 7.6 +1.0wt% Sm2O3,

[0025] The preparation method is as follows: firstly, metal samarium with a purity of 99.9wt%, metal cobalt, pure iron rod, electrolytic copper and metal zirconium are prepared according to the above proportions; then, they are smelted into alloy ingots. The smelting process parameters of this embodiment are shown in Table 1;

[0026] Table 1. Melting process parameters of Example 1

[0027]

[0028] The powder is crushed and jet milled into fine powder. The parameters of the jet mill are as follows: the speed of the classifying wheel is 3000r / min, the working fluid pressure is 0.5MPa, the grinding chamber pressure is 0.05MPa, and the gas is high-purity nitrogen. Finally, an alloy powder of 3 to 4 mm is obtained; then, the second phase Sm2O3, ZrO2, Sm with a particle size of 100 to 300nm is added to the alloy powder according to the ratio. 0.5 Fe 0.15Cu 0.2 Al 0.15 , and the powders were uniformly mixed under the protection of inert gas; a square green body with a size of 60mm×56mm×52mm was obtained by magnetic field molding and cold isostatic pressing, the molding pressure was 6MPa, and the isostatic pressure was 250MPa; the green body was placed in a tubular sintering furnace for sintering, and the vacuum degree reached 5×10 -3 Pa, sintering temperature is 1090℃~1220℃, keep warm for 60min, then cool down by 20℃ and keep warm for 60min, then quickly cool to room temperature and take out the sample, test the sample density, and after meeting the requirements, place the sample in a tubular sintering furnace for heat treatment, and the vacuum degree reaches 5×10 -3 Pa, heat treatment temperature 810℃, keep warm for 24h, cool to 400℃, keep warm for 10h, cool to room temperature and take out the sample.

[0029] Embodiment 2:

[0030] In this embodiment, the alloy composition is Sm(Co 0.675 Fe 0.22 Cu 0.08 Zr 0.025 ) 7.6 +1.5wt% (Sm2O3) and mix the powders evenly; the rest is the same as Example 1.

[0031] Embodiment 3:

[0032] In this embodiment, the alloy composition is Sm(Co 0.675 Fe 0.22 Cu 0.08 Zr 0.025 ) 7.6 +2.0wt% (Sm2O3) and mix the powders evenly; the rest is the same as Example 1.

[0033] Embodiment 4:

[0034] In this embodiment, the alloy composition is Sm(Co 0.65 Fe 0.27 Cu 0.06 Zr 0.02 ) 7.2 +1.0wt% (ZrO2) and mix the powders evenly; the rest is the same as Example 1.

[0035] Embodiment 5:

[0036] In this embodiment, the alloy composition is Sm(Co 0.65 Fe 0.27 Cu 0.06 Zr 0.02 ) 7.2+1.5wt% (ZrO2) and mix the powders evenly; the rest is the same as Example 1.

[0037] Embodiment 6:

[0038] In this embodiment, the alloy composition is Sm(Co 0.65 Fe 0.27 Cu 0.06 Zr 0.02 ) 7.2 +3.0wt% (ZrO2) and mix the powders evenly; the rest is the same as Example 1.

[0039] Comparative Example 1

[0040] In this comparative example, the alloy composition is Sm(Co 0.675 Fe 0.22 Cu 0.08 Zr 0.025 ) 7.6 In this example, no second phase powder is added, and the rest is the same as Example 1.

[0041] Comparative Example 2

[0042] In this embodiment, the alloy composition is Sm(Co 0.675 Fe 0.22 Cu 0.08 Zr 0.025 ) 7.6 +3.0wt% (Sm2O3), the powders are uniformly mixed, and the rest is the same as Example 1.

[0043] Comparative Example 3

[0044] In this comparative example, the alloy composition is Sm(Co 0.65 Fe 0.27 Cu 0.06 Zr 0.02 ) 7.2 +0.5wt% (ZrO2), the powders are uniformly mixed, and the rest is the same as Example 1.

[0045] Comparative Example 4

[0046] In this comparative example, the alloy composition is Sm(Co 0.65 Fe 0.27 Cu 0.06 Zr 0.02 ) 7.2 +3.5wt% (ZrO2), the powders are uniformly mixed, and the rest is the same as Example 1.

[0047] Comparative Example 5

[0048] In this comparative example, the alloy composition is Sm(Co0.65 Fe 0.27 Cu 0.06 Zr 0.02 ) 7.2 +1.0wt%(Sm 0.5 Fe 0.15 Cu 0.2 Al 0.15 ), the powders are uniformly mixed, and the rest is the same as in Example 1.

[0049] The magnetic properties and mechanical strength of the permanent magnets obtained in the above embodiments and comparative examples were tested. B r , i H c 、( BH ) max The magnetic properties test is based on GB / T3217-2013 "Magnetic Test Methods for Permanent Magnetic (Hard Magnetic) Materials" and is measured using a PFM12 pulse magnetic field magnetometer. F 10×10mm cylindrical samples were measured at 23°C. The flexural strength was measured according to GB / T31967.2-2015 "Test methods for physical properties of rare earth permanent magnet materials Part 2: Determination of flexural strength and fracture toughness", using Sansi Zongheng UTM6104X universal testing machine (tension and compression loading module), and the sample size was h × b × L =5×6×20mm, the loading rate is 0.1mm / min, and the results are shown in Tables 2 and 3.

[0050] Table 2. Magnetic properties test results

[0051]

[0052] Table 3. Comparison of bending strength between each embodiment and each comparative example

[0053]

[0054] It can be seen from Comparative Examples 1 and 2 in Table 2 and Table 3 that, under the premise of using the same preparation process, compared with not adding Sm2O3 second phase particles, adding 1.0wt% Sm2O3 second phase particles, the magnetic properties of the magnet have no obvious change, and the bending strength values ​​of the magnet are significantly improved; it can be obtained from Comparative Example 1 and Examples 1, 2, and 3 that under the premise of using the same preparation process, after adding the content of Sm2O3 second phase particles exceeding the optimal value (2 wt%), the pinning effect of Sm2O3 second phase particles in the magnet alloy structure is no longer enhanced, and the refinement effect on the alloy structure is no longer enhanced, which is manifested as the bending strength of the magnet no longer increases. On the contrary, excessive addition will lead to a decrease in the proportion of the magnetic main phase, and the magnetic properties of the magnet will show a significant decrease. Similarly, adding ZrO2 second phase particles to the alloy has a similar rule. Different types of second phase particles, when added to the alloy at the same content, show different gain effects. Compared with Sm2O3 second phase particles, ZrO2 has a more obvious weakening effect on the magnetic properties of the alloy.

[0055] It can be seen from the examples in Table 2 and Table 3 that adding a certain amount of second phase particles can improve the magnetic properties of the alloy ( BH ) max ³24MGOe), the strength of the alloy mechanics in three different test directions has been significantly improved, the maximum bending strength of the magnet alloy has reached nearly 200MPa, and the maximum difference of the magnet in three directions is less than 25MPa, which significantly improves the bending strength of the magnet in three directions and reduces the difference in magnet strength caused by anisotropy; Compared with the embodiment, the auxiliary phase alloy Sm is added 0.5 Fe 0.15 Cu 0.2 Al 0.15 The three-directional bending strength of the magnet has been improved, but the maximum difference in the three directions is large.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-performance, low-mechanical anisotropy rare earth permanent magnet, characterized in that: The raw materials used are composed of a main alloy and a second phase alloy, wherein the chemical composition of the main alloy is Sm(Co bal Fe x Cu y Zr k ) z , where z=6.90~8.0, x=0.10~0.34, y=0.05~0.1, k=0.01~0.03, bal+x+y+k=1, the second phase alloy is Sm2O3; The amount of Sm2O3 added is 1.0-2.0wt% of the main alloy; The particle size of the Sm2O3 is 100-300 nm; The steps of the preparation method include main alloy batching, main alloy smelting into alloy ingot, main alloy crushing, main alloy grinding, adding second phase alloy, mixing, molding, sintering and heat treatment.

2. The high performance, low mechanical anisotropy rare earth permanent magnet according to claim 1, characterized in that: The raw materials used are samarium metal with a purity of 99.9wt%, cobalt metal, pure iron rod, and electrolytic copper.

3. The high performance, low mechanical anisotropy rare earth permanent magnet according to claim 1, characterized in that: The main alloy abrasive adopts air flow mill, and the parameters of the air flow mill are: the speed of the work separation wheel is 2000-6000r / min, the working fluid pressure is 0.4-0.8MPa, the grinding chamber pressure is 0.02-0.06MPa, and the gas adopts high-purity nitrogen, and finally 2-5mm alloy powder is obtained.

4. The high performance low mechanical anisotropy rare earth permanent magnet according to claim 1, characterized in that: The mixed materials are uniformly mixed under the protection of inert gas, and steel balls with a ball radius of 8 to 15 mm are added to the mixing tank. The amount of steel balls added is steel ball mass / powder mass = 1 / 2 to 1 / 3, and the mixing time is not less than 8 hours.

5. The high performance low mechanical anisotropy rare earth permanent magnet according to claim 1, characterized in that: The forming is magnetic field forming, using a semi-automatic magnetic field forming press to magnetic field-form the uniformly mixed alloy powder into blocks or cylinders, and then cold isostatic pressing is performed to obtain a green body; the magnetizing current used is 60-80A, the demagnetizing current is 20-30A, the forming pressure is 5-12MPa, and the isostatic pressure is 200-250MPa.

6. The high performance low mechanical anisotropy rare earth permanent magnet according to claim 1, characterized in that: The vacuum degree during the sintering process is better than 5×10 -3 Pa, keep the sintering temperature at 1090-1220°C for 0.5-2h, cool to 1000-1198°C for solution treatment, keep it for 0.5-2h, quickly cool to room temperature, and finally obtain a solid solution magnet.

7. The high performance low mechanical anisotropy rare earth permanent magnet according to claim 1, characterized in that: The vacuum degree during the heat treatment process is better than 5×10 -3 Pa, keep the heat treatment temperature at 790-810°C for 20-30h, cool to 380-420°C, keep it for 10-20h, cool to room temperature, and obtain the final magnet sample.

Citation Information

Patent Citations

  • Manufacturing method of high-mechanical-strength sintered neodymium iron boron permanent magnets

    CN102568738A

  • Main and auxiliary phase alloy samarium-cobalt magnet material, material for sintered body, and preparation method and application of main and auxiliary phase alloy samarium-cobalt magnet material

    CN113517104A

  • High-strength R-T-B rare earth permanent magnet and preparation method thereof

    CN113936880A

  • Rare-earth-cobalt-based composite material

    CN106531384A